Os impactos sociais e econômicos da previdência social rural no município de Silveira Martins, RS - Schiefelbein, Adriana (2011)
This dissertation delas with research on the impact of the Rural Social Security for the town of Silveira Martins in the maintenance of family agriculture, thiscity was chosen because this has a high percentage of beneficiaries of public policy compared with the total population of the town. The Social Security benefit is an important role in the spatial configuration and spatial reproduction of the city under study. The selected theme is to analyze the importance ofstudy. The selected theme is to analyze the importance of Social Security funds in the maintenance of family farmers in the productive unit. The elderlyrepresent a significant portion ofthe economy.